Analysis of Pharmaceutical Staffing Needs in the Pharmacy Installation of Grha Permata Ibu Hospital Depok 2016 - Verawaty Verawaty; M. Ihsan Ramdani; Diah Ratih Laksmitawati; Christine Meidiawati (Faculty of Pharmacy, Universitas Gadjah Mada)
The potential incident of medication error in pharmacy unit might arise due to increased workload of pharmacy staff. Excessive workload triggers exhaustion and lack of concentration of the pharmacy staff in pharmacy services. Increasing the number of pharmacy staff is the solution to reduce workload, therefore analysis of workload of pharmacy staff at Graha Permata Ibu Hospital’s pharmacy unit (IFRS GPI) is required to be used in calculating the ideal and productive needs of staff, which is also the purpose of this study. This study is a combination of qualitative and quantitative research with samples from pharmacy personnel activities. The techniques of data collection were obtained through observation using work sampling and in-depth interviews. Data were analyzed using Workload Indicators of Staffing Need (WISN).The result showed direct productive activities amounted to 59.14%, indirect productive activities amounted to 17.22%, 16.99% of non-productive activities, and 6.65% of personnel private activities. Pharmacy staffing need is 26 people. The ratio comparison between existing personnel and staffing need of the pharmacy installation was 0.7, which indicates the numbers of pharmacy personnel are not in accordance with the workload. It concludes a few necessities such as a need for new hires of pharmacy personnel, a new arrangement of work shifts and scheduling, a modification of service flow for requested prescription, a need to maximize the utilization of hospital information systems, a need to increase the role of pharmacists, and to conduct education and continuous training.